Immunization calculation engine: An open source immunization evaluation and forecasting system. Issue 1 (7th July 2021) - Arzt, Noam H.; Chertcoff, Daryl; Nicolary, Samuel; Suralik, Michael; Berry, Michael
Abstract: Introduction: The immunization calculation engine (ICE) is a free, open‐source immunization forecasting evaluation and software system whose default immunization schedule supports all routine childhood, adolescent, and adult immunizations based on the recommendations of the Advisory Committee on Immunization Practices (ACIP). ICE utilizes its immunization rules and patient data to evaluate and return the validity of each immunization in the patient's history along with one or more evaluation reasons. It also returns a recommendation for each vaccine group along with one or more recommendation reasons. Methods: In January 2020, ICE was first released as a Docker image along with the traditional zip archive file which had been used up to that point. Docker enables software providers to easily distribute their software so that it can be run "out of the box" in the user's local environment. Software running in Docker containers drastically reduces the complexity of software distribution and set up. Results: Clinical systems of many types use ICE. The project began within the public health arena as a feature of Immunization Information Systems (IIS), but electronic health records (EHR) and personal health records (PHR) have also deployed ICE. While it is not possible to identify the specific impact of ICE on clinical care without additional research, it should be pointed out that once deployed within an IIS, EHR, or PHR the display of ICE results is performed for every patient viewed by a user and often for every patient appearing on a report. In a typical month, thousands if not millions of evaluations and forecasts are performed by ICE and displayed to the users. Conclusions: The ICE Project believes in minimizing the barriers to installing and using ICE anywhere. To that end, there is no registration required to download the source code or runtime code for the ICE service and its default rule. Similarly, the Project created a Docker image of ICE to facilitate easy and seamless implementation.